2006
DOI: 10.1074/jbc.m510798200
|View full text |Cite
|
Sign up to set email alerts
|

The Substrate-induced Conformational Change of Mycobacterium tuberculosis Mycothiol Synthase

Abstract: The structure of the ternary complex of mycothiol synthase from Mycobacterium tuberculosis with bound desacetylmycothiol and CoA was determined to 1.8 Å resolution. The structure of the acetylCoA-binary complex had shown an active site groove that was several times larger than its substrate. The structure of the ternary complex reveals that mycothiol synthase undergoes a large conformational change in which the two acetyltransferase domains are brought together through shared interactions with the functional g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 19 publications
3
44
0
Order By: Relevance
“…The GNAT domain functions as the binding site for the substrate acetyl-CoA. MshD contains two GNAT domains at amino acids 1 to 140 and at amino acids 151 to 315 (27,28). The C-terminal GNAT domain contains the catalytic site, while the N-terminal domain contributes to the structural stability of the protein (28).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GNAT domain functions as the binding site for the substrate acetyl-CoA. MshD contains two GNAT domains at amino acids 1 to 140 and at amino acids 151 to 315 (27,28). The C-terminal GNAT domain contains the catalytic site, while the N-terminal domain contributes to the structural stability of the protein (28).…”
Section: Resultsmentioning
confidence: 99%
“…Shortly thereafter, the crystal structure of the M. tuberculosis acetyl-CoA-MshD complex was reported (27), and the recent structural analysis of a ternary complex produced from CysGlcN-Ins and CoA provides insights into the conformational changes involved in catalysis (28). Transposon site hybridization studies identified this gene (Rv0819) as nonessential for the growth of M. tuberculosis (23).…”
mentioning
confidence: 99%
“…It appears to have two separate regions with similarity to the pfam00583 domain for acetyltransferase and is approximately twice the size of homologous proteins, indicating that MshD is the result of a gene duplication (59). Blanchard and coworkers (147) Kinetic studies indicated a ternary complex mechanism common to the GNAT superfamily of N-acetyltransferases in which both substrates must be present for the reaction to occur (148). Based upon the crystal structure of the mixed disulfide of Cys-GlcN-Ins and CoA and the pH dependence of enzyme activity, the catalytic mechanism shown in Fig.…”
Section: Mshd the Msh Synthase (Msh Acetyltransferase)mentioning
confidence: 99%
“…MshD is also likely to be a drugable target considering the substantial surfaces involved in the binding of the substrate moieties (148). The mshD mutant produces a small amount of MSH as well as a substantial level of formyl-Cys-GlcN-Ins, and the mshD gene is not essential for growth of M. tuberculosis (13).…”
Section: Msh Drug Targets In Mycobacterium Tuberculosismentioning
confidence: 99%
“…Therefore MshA and MshC are important potential drug targets for treatment of tuberculosis and other Actinomycetales infections. The three-dimensional structures of both MshB (19) and MshD (20,21) have been determined; however, there have been no reports of structures for MshA or MshC.…”
mentioning
confidence: 99%